PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI BERPRESTASI TERHADAP KINERJA - , T IVANA ELITASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In their efforts to realize X University visions and missions, all members of the university need to perform well at work. The working performance of an employee can be measured by completed tasks based on the given standard of measurement in a certain period of time. A number of factors affecting the employeesâ performance at work exist, including transformational leadership and motivation for achievement. This study aims to test the effect of transformational leadership and motivation for achievement on the working performance of the employees. Questionnaires were used to collect the data. As many as 82 questionnaires were sent to respondents, employees at the Faculty of Languages and Arts of X University, and 70 of them were returned to the researcher. The data were then analyzed by using double regression test. The research has revealed that transformational leadership and motivation for achievement significantly affect the working performance as much as 52.2%, whereas other variables affect the employees working performance as much as 44.8%. The double regression test indicates that both transformational leadership and motivation for achievement significantly affect the employeesâ working performance, whereas motivation for achievement partially affects their working performance.